Wood-Water Interactions as Affected by Chemical Constituents of Woods - TURGUT SAHIN, HALIL (Asian Journal of Chemistry, 2010)
The results indicate that the chemical constituents of woods have considerable effects on wood-water interactions. Pine, poplar and eucalyptus woods show more or less expected swelling properties. However, cedar, which has the highest density, shows considerably less swelling (6.3 %) and very low activation energy (21.4 Kj/mol) compared with other woods. This clearly reveals cedar's chemical composition contributes to its anomalous swelling behaviour in water. The results prove the potential use of the chemical constituents of wood in predicting the swelling and water-sorption properties on the basis of its both density and chemical composition. However, cellulose content can be better predicted by the activation-energy relationship of different woods. A significant increase in the water sorption and swelling properties was observed in the four different wood species after the removal of their extractives.